2010
DOI: 10.1080/00223891003670232
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Characteristics of the Dissociation Tension Scale

Abstract: The newly developed Dissoziations-Spannungs-Skala (Dissociation Tension Scale; DSS) is a self-rating instrument for the assessment of psychological and somatoform dissociative features (ranging from normal up to pathological) as well as aversive inner tension occurring within the past 7 days. The DSS contains 21 items assessing dissociative symptoms and 1 additional item assessing aversive inner tension. Ratings are made on a time-oriented scale ranging from 0% (never) to 100% (constantly). We measured the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 33 publications
1
46
0
4
Order By: Relevance
“…23,26 However, state dissociation and aversive inner tension before the experiment were relatively low compared with previous findings. 24 Among all patients with BPD, 5 also had social phobia and 4 met the criteria for an eating disorder. Of the participants with comorbid PTSD, 3 had social phobia and 4 had an eating disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23,26 However, state dissociation and aversive inner tension before the experiment were relatively low compared with previous findings. 24 Among all patients with BPD, 5 also had social phobia and 4 met the criteria for an eating disorder. Of the participants with comorbid PTSD, 3 had social phobia and 4 had an eating disorder.…”
Section: Resultsmentioning
confidence: 99%
“…23 ‡Assessed by use of Dissociation Tension Scale-acute. 24 §Assessed by use of Borderline Symptom List. 26 …”
Section: Script-driven Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…28 In patients with BPD, dissociative symptoms were assessed using the Dissociative Tension Scale (DTS). 29 The control group included unmedicated women matched for age, education and handedness. Participants with a neurologic or psychiatric disorder according to DSM-IV criteria or any substance abuse or dependence were excluded.…”
Section: Participantsmentioning
confidence: 99%
“…Dissociative symptoms (e.g., detachment from physical and emotional experiences) are also highly present in BPD and may influence psychological reactions to emotional stimuli (e.g., Barnow et al, 2010;Korzekwa, Dell, Links, Thabane, & Fougere, 2009;Stiglmayr, Braakmann, Haaf, Stieglitz, & Bohus, 2003). Research has demonstrated that if dissociation functions as a conditioned emotion regulation strategy, it becomes an automatized response to even minor stressors, which interferes with the processing of emotional information (e.g., Oathes & Ray, 2008;Schore, 2009).…”
mentioning
confidence: 99%